2013
DOI: 10.4161/onci.22890
|View full text |Cite
|
Sign up to set email alerts
|

Vemurafenib enhances MHC induction inBRAFV600Ehomozygous melanoma cells

Abstract: To optimally integrate targeted kinase inhibitors and immunotherapies in the treatment of melanoma, it will be critical to understand how BRAFV600E mutational status and BRAFV600E inhibition influence the expression of genes that govern antitumor immune responses. Because major histocompatibility complex (MHC) molecules are critical for interactions between tumor cells and lymphocytes, we investigated the impact of BRAFV600E-selective inhibitors on the expression of MHC molecules. We found that the treatment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
112
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(118 citation statements)
references
References 44 publications
4
112
1
1
Order By: Relevance
“…Therapeutics augmenting NLRC5 activity could compensate for this deficit by breaking cancer immune evasion in a broad range of tumor types. Interestingly, it has been reported that currently used therapies, such as an EGF receptor inhibitor (cetuximab) or a B-Raf inhibitor (vemurafenib), enhance MHC class I expression via IFN-γ (35,36). Therefore, these currently available therapies, originally designed to disrupt oncogenic signaling, may mediate their effects in part via the NLRC5-dependent MHC class I pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutics augmenting NLRC5 activity could compensate for this deficit by breaking cancer immune evasion in a broad range of tumor types. Interestingly, it has been reported that currently used therapies, such as an EGF receptor inhibitor (cetuximab) or a B-Raf inhibitor (vemurafenib), enhance MHC class I expression via IFN-γ (35,36). Therefore, these currently available therapies, originally designed to disrupt oncogenic signaling, may mediate their effects in part via the NLRC5-dependent MHC class I pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Molecularly targeted agents are also being combined with immune checkpoint inhibitors. BRAF inhibition, which is FDA-approved for the treatment of metastatic melanoma expressing the activating BRAF V600E mutation, has been shown to increase MHC expression, tumor antigen presentation, and T-cell infiltration (98)(99)(100)(101)(102). Similarly, MEK inhibitors have been shown to improve CD8+ T-cell activity in preclinical models in combination with PD-1 blockade (103).…”
Section: Future Directionsmentioning
confidence: 99%
“…C recurrent Grade II gliomas (NCT02193347); (6) the safety and efficacy of peptides derived from indoleamine 2,3-dioxygenase 1 (IDO1) [202][203][204][205][206] combined with the FDA-approved immune checkpoint blocker ipilimumab (also known as Yervoy TM ) [207][208][209][210][211][212] and vemurafenib (an FDA-approved inhibitor of mutant BRAF) [213][214][215][216][217] are being evaluated in melanoma patients (NCT02077114); (7) the therapeutic profile of a CMP targeting ganglioside GD2 and the so-called Lewis Y antigen (2 non-peptide TAAs), [218][219][220] employed as a PADRE-and Montanide ISA-51-adjuvanted intervention in combination with standard chemotherapy, is being assessed in breast carcinoma patients (NCT02229084); (8) full-length, recombinant cancer/ testis antigen 1B (CTAG1B, best known as NY-ESO-1)…”
Section: Gm-csf-adjuvanted Standalone Interventions In Subjects Bearimentioning
confidence: 99%